2015
DOI: 10.1007/s10899-014-9519-5
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Metacognition in Pathological Gambling: A Mediation Model

Abstract: Pathological gambling involves multitudinous costs related to financial, legal, and public health care aspects, as well as to specific psychological disorders. Despite the overall evidence suggesting that comorbid disorders represent a risk factor for pathological gambling, there is scant evidence on the appropriate treatments for gamblers with such disorders. In this context, metacognitive therapy is an interesting approach because it considers psychological disorders as a result of the activation of persever… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 33 publications
(10 citation statements)
references
References 29 publications
0
9
0
1
Order By: Relevance
“…Interestingly, mindfulness is negatively related to GD severity ( Lakey, Campbell, Brown, & Goodie, 2007 ; Reid, Di Tirro, & Fong, 2014 ; Riley, 2012 ), suggesting that PGs may have a deficit in the ability to accept emotional states in a non-judgmental way. In addition, studies on metacognition capacities among PGs provided preliminary evidence that GD severity may be related to positive beliefs toward the need to control thoughts ( Jauregui, Urbiola, & Estevez, 2016 ; Lindberg, Fernie, & Spada, 2011 ; Mansueto et al., 2016 ; Spada & Roarty, 2015 ). PGs often believe that certain types of thoughts have to be suppressed, and this has been demonstrated by Riley ( 2012 ), which reported high levels of thought suppression among PGs.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, mindfulness is negatively related to GD severity ( Lakey, Campbell, Brown, & Goodie, 2007 ; Reid, Di Tirro, & Fong, 2014 ; Riley, 2012 ), suggesting that PGs may have a deficit in the ability to accept emotional states in a non-judgmental way. In addition, studies on metacognition capacities among PGs provided preliminary evidence that GD severity may be related to positive beliefs toward the need to control thoughts ( Jauregui, Urbiola, & Estevez, 2016 ; Lindberg, Fernie, & Spada, 2011 ; Mansueto et al., 2016 ; Spada & Roarty, 2015 ). PGs often believe that certain types of thoughts have to be suppressed, and this has been demonstrated by Riley ( 2012 ), which reported high levels of thought suppression among PGs.…”
Section: Resultsmentioning
confidence: 99%
“…Again, research on metacognitions among PGs brought interesting results. Some studies indicate that PGs have high levels of positive beliefs toward the use of perseverative thinking ( Jauregui, Urbiola, et al., 2016 ; Mansueto et al., 2016 ; Spada & Roarty, 2015 ). More closely related to the addictive behavior, it seems that, as previously discussed for alcohol drinking ( Cooper, Frone, Russell, & Mudar, 1995 ; Garofalo & Velotti, 2015 ), PGs have high expectancies toward the efficiency of gambling as a regulatory strategy.…”
Section: Resultsmentioning
confidence: 99%
“…Second, it has been demonstrated that metacognitions are involved in several problematic behaviors, including traditional addictive behaviors (e.g., problem drinking and smoking), established behavioral addictions (i.e., gambling), and potential behavioral addiction such as PIU and problematic gaming (Mansueto et al, 2016;Spada & Caselli, 2017;Spada, Caselli, & Wells, 2009;Spada, Nikčević, Moneta, & Wells, 2007). Therefore, we want to test whether metacognitions are directly linked to PFU in adolescents:…”
Section: Aims Of This Studymentioning
confidence: 99%
“…De hecho, algunos autores han propuesto que los factores motivacionales sesgan las cogniciones sobre el juego, como predicen los modelos de razonamiento motivado (Navas et al, 2016). Por tanto, la conciencia de problemas podría ser sensible a estrategias de entrenamiento en habilidades metacognitivas (Mansueto et al, 2016).…”
Section: Implicaciones Clínicasunclassified